Gentisic acid prevents diet-induced obesity in mice by accelerating the thermogenesis of brown adipose tissue. Issue 3 (12th January 2021) - Han, Xue; Guo, Jielong; Gao, Yunxiao; Zhan, Jicheng; You, Yilin; Huang, Weidong
Abstract : Gentisic acid prevents diet-induced obesity in mice by accelerating the thermogenesis of brown adipose tissue. Abstract : Since obesity occurs when energy intake is higher than energy expenditure, increasing energy expenditure is an effective strategy to prevent or treat obesity. Brown adipose tissue (BAT) is a classic energy-consuming organ whose thermogenesis function can be activated by dietary components. Gentisic acid (2, 5-dihydroxybenzoic acid, (DHB)) is widely found in food and exhibits many physiological functions, which include anti-inflammatory, antimicrobial, antioxidant, and hepatoprotective properties. However, its anti-obesity effect and mechanism have yet to be examined. This study investigated the effect and mechanism of DHB in preventing diet-induced obesity in mice from the perspective of energy metabolism. The C57BL/6 mice were fed a normal diet (ND), a high-fat and high-fructose diet (HFFD) or HFFD plus 2 mg mL −1 DHB (DHB + HFFD) for 12 weeks. Measuring obesity, lipid metabolism, energy metabolism and BAT related indicators. Moreover, the C3H10T1/2 cells were used to assess the effect of DHB on brown adipocytes in vitro . The results proved that, at the end of the experiment, the body weight of the mice in the DHB + HFFD group was 14.97% lower than in the HFFD group. DHB reduced the weight of the major organs, improved insulin sensitivity, and decreased systemic lipid accumulation. Moreover, DHB administration significantly increased energy metabolism, which was (partly) due to the activation of BAT thermogenesis. Furthermore, DHB supplementation enhanced the expression of the fatty acid oxidation related proteins in BAT and the brown adipocytes, indicating that DHB augmented the utilization of fatty acids by BAT, which is the primary substance of thermogenesis. This study reveals that DHB administration prevents HFFD induced obesity in mice by (at least partly) accelerating the oxidation of fatty acids and stimulating the thermogenesis of BAT.